2017
DOI: 10.1371/journal.pone.0184199
|View full text |Cite
|
Sign up to set email alerts
|

Success of a weight loss plan for overweight dogs: The results of an international weight loss study

Abstract: IntroductionObesity is a global concern in dogs with an increasing prevalence, and effective weight loss solutions are required that work in different geographical regions. The main objective was to conduct an international, multi-centre, weight loss trial to determine the efficacy of a dietary weight loss intervention in obese pet dogs.MethodsA 3-month prospective observational cohort study of weight loss in 926 overweight dogs was conducted at 340 veterinary practices in 27 countries. Commercially available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 34 publications
7
24
1
8
Order By: Relevance
“…The mean age value was numerically higher in group 2, but did not differ statistically from group 1, because 67% of dogs in group 2 were aged 1 to 5 years. In a study of international scope, the researchers also observed obesity in dogs from 1-year-old [6]. In the present study, young adult dogs presented excess body fat, compatible with overweight or obesity, possibly, due to early neutered associated with ad libitum feeding.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The mean age value was numerically higher in group 2, but did not differ statistically from group 1, because 67% of dogs in group 2 were aged 1 to 5 years. In a study of international scope, the researchers also observed obesity in dogs from 1-year-old [6]. In the present study, young adult dogs presented excess body fat, compatible with overweight or obesity, possibly, due to early neutered associated with ad libitum feeding.…”
Section: Discussionsupporting
confidence: 68%
“…In the present study, group 2 was initially formed and all dogs in this group were neutered and presented overweight or obese; agreeing with epidemiological studies that evaluated the canine obesity [2,6,8]. Then, to compose group 1, which would represent the control situation, dogs were recruited with ideal BCS and also neutered.…”
Section: Discussionmentioning
confidence: 90%
“…Contingency tables were used to assess the independence of the effect of each factor on percentage weight loss compared with all other factors. Stepwise regressions were set in such a way that each forward selection step could be followed by a backward elimination step if necessary using the Schwarz Bayesian Information Criterion (SBC) [ 28 , 29 ]), as previously described [ 30 ]. Complementary analysis of baseline data was performed using a classic general linear model (GLM) to assess the effect of the most relevant factors identified in the stepwise regression.…”
Section: Methodsmentioning
confidence: 99%
“…While one recent study performed in Danish dogs found an increased obesity risk associated with desexing that was limited to male dogs [189], most other available studies find that the effect is present in both sexes. In addition, an international study of 926 overweight dogs undergoing a weight loss diet for three months found that intact dogs of both sexes lost significantly more weight during the study period than desexed dogs [192].…”
Section: Weight Gain and Obesitymentioning
confidence: 99%